2004
DOI: 10.1002/polb.10763
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of introducing of catalytic centers into layer galleries of layered silicates and related epoxy nanocomposites. I. Epoxy nanocomposites derived from montmorillonite modified with catalytic surfactant‐bearing carboxyl groups

Abstract: Montmorillonite (MMT) was modified with the acidified cocamidopropyl betaine (CAB) and the resulting organo‐montmorillonite (O‐MMT) was dispersed in an epoxy/methyl tetrahydrophthalic anhydride system to form epoxy nanocomposites. The intercalation and exfoliation behavior of the epoxy nanocomposites were examined by X‐ray diffraction and transmission electron microscopy. The curing behavior and thermal property were investigated by in situ Fourier transform infrared spectroscopy and DSC, respectively. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…Before the suspensions were acidified, the carboxyl groups were dissociated, as indicated by the pH range (8.0-8.3) of these suspensions, thus rendering the surfactant molecules electrically neutral. An earlier report on the intercalation of CAB into montmorillonite mentions acidifying the surfactant to an unspecified pH prior to mixing with the clay [14] and this is usual practice when working with alkylamines in the form of the free base [5]. Although it might be anticipated that a dissociated, negatively charged carboxyl group might hinder the uptake, these results indicate that greater uptake can result without acidifying the suspension.…”
Section: Experiments 2: Effect Of Phmentioning
confidence: 71%
See 2 more Smart Citations
“…Before the suspensions were acidified, the carboxyl groups were dissociated, as indicated by the pH range (8.0-8.3) of these suspensions, thus rendering the surfactant molecules electrically neutral. An earlier report on the intercalation of CAB into montmorillonite mentions acidifying the surfactant to an unspecified pH prior to mixing with the clay [14] and this is usual practice when working with alkylamines in the form of the free base [5]. Although it might be anticipated that a dissociated, negatively charged carboxyl group might hinder the uptake, these results indicate that greater uptake can result without acidifying the suspension.…”
Section: Experiments 2: Effect Of Phmentioning
confidence: 71%
“…Fully exfoliated epoxy-montmorillonite nanocomposites were obtained in which the betaine had a catalytic effect on the resin curing, as shown by the faster disappearance of the epoxy ring with increasing clay loading. It has been suggested that such interactions took place when CAB-organoclays were compounded with epoxy resin by in-situ intercalative polymerization [14] where the carboxyl group demonstrated a catalytic effect on polymerization, indicating that the carboxyl group can interact with the matrix. For this to occur requires that the carboxyl group should be protonated, which was ensured by acidifying the clay-surfactant suspension.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also been shown that the carboxyl group in CAB-MMT organoclay can catalyse curing in epoxy resins [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hwu et al reported that the intercalated nanocomposite prepared by the solution method shows a higher glass transition temperature (T g ) and a higher T d [19]. On the other hand, the nanocomposites of acid anhydridecured epoxy resins can be prepared by essentially in situ intercalative polymerization method [20][21][22][23][24][25][26][27] because the cured polymers are non-fusible and insoluble. For example, Zhang et al reported that the nanocomposite prepared from diglycidyl ether of bisphenol A and 4-methyl-1,2-cyclohexanedicarboxylic dianhydride shows a higher T g , T d and storage modulus than the pure cured epoxy resin [21].…”
Section: Introductionmentioning
confidence: 99%